Investment of Religious Value of Problemed Students in MA Muhammadiyah 5 Pulung Ponorogo - Fadhlurrahman Fadhlurrahman; Tri Yaumil Falikah; Fandi Akhmad (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
Problems in the world of education are increasingly worrying, it is necessary to immediately make improvements from all lines in the world of education. Including students with problems in school. should get treatment immediately. The purpose of this article is to examine the problems of problematic students at MA Alam Muhammadiyah 5 Pulung, Ponorogo. Troubled students are increasingly different. Both from trivial problems to big problems. This school is able to turn problem students into better students than before. The method in this article is a case study. Researchers looked closely at the case and its handling. The results in this study are the inculcation of religious values must be in the form of (a) consistent teacher exemplary, (b) the teacher's personal approach to students, (c) the habit of doing good to students and (d) no need for punishment. So with the treatment carried out by MA Alam Muhammadiyah Pulung, Ponorogo can be applied in other schools.